2018
DOI: 10.1055/a-0753-0259
|View full text |Cite
|
Sign up to set email alerts
|

When Are Trainees Ready to Perform Transvaginal Ultrasound? An Observational Study

Abstract: Purpose The purpose of this study was two-fold: (1) To determine how the number of ultrasound scans a trainee has completed predicts the trainee’s diagnostic accuracy when performing transvaginal ultrasound examinations, and (2) to examine the utility of simulation-based assessment of ultrasound competence for determining readiness for independently performing examinations. Materials and Methods 101 OB/GYN trainees were surveyed regarding their clinical experience and the number of scans they had com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 20 publications
2
7
0
Order By: Relevance
“…First, the simulation-based training provided in this study is a very brief intervention relative to the presumably large volume of scans completed by the experienced obstetricians. Our findings, therefore, give further credence to the concern raised in recent studies regarding the reliability of volume of scans as a measure of competence in ultrasound 3,5 . Second, according to some learning theories 13 , structured teaching, such as simulation-based ultrasound training, may have negative effects for experienced obstetricians, who already have inveterate habits in performing obstetric ultrasound 13 .…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…First, the simulation-based training provided in this study is a very brief intervention relative to the presumably large volume of scans completed by the experienced obstetricians. Our findings, therefore, give further credence to the concern raised in recent studies regarding the reliability of volume of scans as a measure of competence in ultrasound 3,5 . Second, according to some learning theories 13 , structured teaching, such as simulation-based ultrasound training, may have negative effects for experienced obstetricians, who already have inveterate habits in performing obstetric ultrasound 13 .…”
Section: Discussionsupporting
confidence: 83%
“…The learning curve is long, and it may be difficult to reach and maintain mastery if training relies on clinical practice alone. In fact, a number of studies have shown that clinical experience does not necessarily ensure competence, which may be explained by a lack of initial systematic training, as well as skill decay over time. Lack of ultrasound competence can cause diagnostic errors that lead to inappropriate obstetric management, which may subsequently have serious implications for patient care and outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to the large time resources required for clinical training, ultrasound examinations can be accompanied by some discomfort for the patient when the ultrasound operator is inexperienced [5]. Insufficient initial training may lead to failure to achieve expert levels of diagnostic certainty regardless of the number of completed scans [6]. For these reasons, there has been an increased focus on more effective methods for ultrasound training such as simulation-based medical education, which in other fields of practice has been shown to result in large improvements in trainee skills and moderate improvements in patient outcomes [7].…”
Section: Introductionmentioning
confidence: 99%
“…5 Despite this, a recent study showed that, while there is an association between number of scans performed and diagnostic accuracy, the number of scans performed is not a sufficiently robust predictor of accuracy to ensure proficiency. 6 As a result of both the time and subjectivity involved in developing ultrasound skills, there is evolving interest in the use of ultrasound simulation training to enable practical skills to be developed at a time and place convenient to trainee and trainer and as an objective and standardised assessment of competency. [6][7][8] Several platforms and systems have been described and are reported to lead to sustained improvements in performance, which can be reproduced in the clinical environment.…”
Section: Introductionmentioning
confidence: 99%
“…6 As a result of both the time and subjectivity involved in developing ultrasound skills, there is evolving interest in the use of ultrasound simulation training to enable practical skills to be developed at a time and place convenient to trainee and trainer and as an objective and standardised assessment of competency. [6][7][8] Several platforms and systems have been described and are reported to lead to sustained improvements in performance, which can be reproduced in the clinical environment. [7][8][9][10][11][12]…”
Section: Introductionmentioning
confidence: 99%